Study of Flexible Pavement Structure Maintenance in Runways with Pavement Condition Index (PCI) Method - Meilinda Atika Rachman; Harmein Rahman; Bambang Sugeng Subagio; Sri Hendarto (Institut Teknologi Bandung, 2020)
AbstractRunway is an area in an airport for aircrafts to land and take off. The maintenance of the facilities on both the airside and landside must be taken care of in order to maximize the performance of the airport. Based on the aircraft type service plan of Balikpapan Sultan Aji Muhammad Sulaiman Sepinggan Airport and to maximize the performance of airports at present and in the future, an assessment of the condition of the runway with a Pavement Condition Index (PCI) value parameter on the flexible pavement to obtain the optimal repair or maintenance needs was carried out. The PCI obtained in 2019 was 61 (fair). Based on the PCI value in the runway, an evaluation was conducted with COMFAA and FAARFIELD to obtain the most critical aircraft PCN value in 2019. Segment 1, which is assumed to be half of the runway length which is sta 0 + 000 to 1 + 250, has a PCN value of 34.3 and segment 2, assumed to be of sta 1 + 250 - 2 + 500, has a PCN value of 33.2 where the ACN value for critical aircraft B777 - 300 ER is 89.3. In accordance with the recommendation of FAA AC-5380-6C, the most optimal scenario is scenario 2, which is major rehabilitation with the handling type of inlay - scrape and fill every 7 years when the PCI value is 49 (poor) and in the following years, routine maintenance would be done with patching. The total handling fee for 20 years of maintenance with scenario 2 is Rp. 195,377,000,000. AbstrakRunway merupakan area pada bandar udara untuk tempat mendarat dan lepas landas bagi pesawat. Fasilitas